THEORETICAL AND ECONOMETRIC ASPECTS OF THE RELATIONSHIP OF MILITARY EXPENDITURES AND ECONOMIC GROWTH - Koval, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article examines the essence of the macroeconomic model "Guns versus Butter" (a compromise between military and other state expenditures) and determines the relevance of its application in the study of the impact of military burden on the economy of Ukraine. In the course of the study, the following indicators were singled out for studying the relationship between military expenditures (expenditure on national security and defense) and social security expenditures (non-defense sector goods that improve public welfare): total GDP, share of GDP on defense (military burden on economy) and other governmental programs, as well as the tax burden. The article segments the main indicators of the state budget of Ukraine for the period 2014–2021, which indicate the processes that develop over time, depending on military, political, economic, geopolitical factors, etc. The results of empirical studies conducted for a number of least developed countries, developing countries and developed countries in different regions of the world testify to "two sides of the same coin", the unity of opposites that ensures the development of the system and its balance. The leading role in this balance is played by the relationship between economic growth and military spending, as well as the methodology for assessing the causal relationship between them. It was found that, depending on the geopolitical situation, potential or existing armed conflicts, military spending can play a key role in the protection of national security and defense, and therefore in economic development and stabilization of public welfare, through investment attractiveness, free market relations, innovative activity etc. The conclusion indicates the need to conduct quantitative micro-, meso-, and macro-economic studies in Ukraine during the period of independence, using methods and models for substantiating economic decisions.
Keywords: GDP, economic growth, military spending, macroeconomic model, military capability